2001
DOI: 10.1161/01.str.32.7.1581
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Magnetic Resonance Imaging Maps in Hyperacute Stroke

Abstract: Background and Purpose-In ischemic stroke, perfusion-weighted imaging (PWI) and diffusion-weighted imaging (DWI) provide important pathophysiological information. A PWIϾDWI mismatch pattern suggests the presence of salvageable tissue. However, improved methods for distinguishing PWIϾDWI mismatch tissue that is critically hypoperfused from benign oligemia are required. Methods-We investigated the usefulness of maps of relative cerebral blood flow (rCBF), volume (rCBV), and mean transit time (rMTT) to predict tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(62 citation statements)
references
References 40 publications
0
60
2
Order By: Relevance
“…Problems with the MRI definition of the penumbra include the fact that there is no threshold within a region of oligemia (Kidwell et al, 2003;Kane et al, 2007;Toth and Albers, 2009), and that the PWI abnormality often overestimates the final infarction volume, and hence the amount of tissue at risk (Parsons et al, 2001). In addition, the initial diffusion lesion does not necessarily define the core of infarcted tissue because some diffusion lesions can be transiently or permanently reversed if blood flow is rapidly restored (Kidwell et al, 2000;Parsons et al, 2002;Chalela et al, 2004).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Problems with the MRI definition of the penumbra include the fact that there is no threshold within a region of oligemia (Kidwell et al, 2003;Kane et al, 2007;Toth and Albers, 2009), and that the PWI abnormality often overestimates the final infarction volume, and hence the amount of tissue at risk (Parsons et al, 2001). In addition, the initial diffusion lesion does not necessarily define the core of infarcted tissue because some diffusion lesions can be transiently or permanently reversed if blood flow is rapidly restored (Kidwell et al, 2000;Parsons et al, 2002;Chalela et al, 2004).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Penumbra in acute stroke is usually investigated by using by the diffusion-perfusion mismatch, which requires a contrast agent injection. [12][13][14][15] We have developed a new neuroradiologic method for imaging the ischemic penumbra in acute stroke patients, based on DWI without the injection of intravenous contrast material. [16][17][18] The penumbra is defined on the initial ADC map by an algorithm based on the topobiology of natural infarct growth and the modeling of ADC abnormalities occurring in the penumbral tissue.…”
mentioning
confidence: 99%
“…The differences in TTP, T max , and MTT for brain parenchyma on the normal and stenotic sides were widely used in diffusion-perfusion mismatch research (7)(8)(9)(10)(11)(12)(13)(17)(18)(19)(20). A delay of more than 4 or 6 s yields a fair estimate of hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A delay of more than 4 or 6 s yields a fair estimate of hypoperfusion. Although prolongation of TTP, T max and MTT is proposed to be related to tissues at risk in diffusion-perfusion mismatch research, recent studies have shown that benign oligemia is included in hyperintense areas observed on TTP (8,(11)(12)(13), T max (13,19,20), and MTT (13,16,17) images. As an example, there is a large bright area on the TTP, T max , and MTT images for the second patient shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation